2015
DOI: 10.1098/rsbl.2014.1058
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genomes reveal the extinct Hippidion as an outgroup to all living equids

Abstract: Hippidions were equids with very distinctive anatomical features. They lived in South America 2.5 million years ago (Ma) until their extinction approximately 10 000 years ago. The evolutionary origin of the three known Hippidion morphospecies is still disputed. Based on palaeontological data, Hippidion could have diverged from the lineage leading to modern equids before 10 Ma. In contrast, a much later divergence date, with Hippidion nesting within modern equids, was indicated by partial ancient mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
32
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 22 publications
9
32
2
Order By: Relevance
“…francisci (= E. francisci) to extant Equus than primitive species of the genus, such as E. simplicidens (= E. shoshonensis) and E. stenonis, is also indicated by cranial proportions (Eisenmann and Baylac, 2000). Ancient mitochondrial DNA analyses suggested that the lineage which was later named Haringtonhippus was the sister species to extant and fossil caballine equids (Weinstock et al, 2005;Orlando et al, 2008;Vilstrup et al, 2013;Der Sarkissian et al, 2015;Barrón-Ortiz et al, 2017). In contrast to these results, a recent genomic analysis concluded that Ha.…”
Section: Phylogenetic Analysismentioning
confidence: 92%
“…francisci (= E. francisci) to extant Equus than primitive species of the genus, such as E. simplicidens (= E. shoshonensis) and E. stenonis, is also indicated by cranial proportions (Eisenmann and Baylac, 2000). Ancient mitochondrial DNA analyses suggested that the lineage which was later named Haringtonhippus was the sister species to extant and fossil caballine equids (Weinstock et al, 2005;Orlando et al, 2008;Vilstrup et al, 2013;Der Sarkissian et al, 2015;Barrón-Ortiz et al, 2017). In contrast to these results, a recent genomic analysis concluded that Ha.…”
Section: Phylogenetic Analysismentioning
confidence: 92%
“…Mitochondrial genomes (mitogenomes) generally provide much higher phylogenetic resolution than traditionally used morphological and single gene-based molecular markers (Nie et al, 2018), so mitochondrial phylogenomics is increasingly used to tackle phylogenetic controversies (Bourguignon et al, 2018; Cameron, 2014; Der Sarkissian et al, 2015; Lan et al, 2017; Li et al, 2017). Although the resolution of this approach is still limited by a very small number of available mitogenomes in isopods, overview of published studies shows that they also failed to produce results congruent with other approaches, failed to resolve the rogue taxa issues, and taken as a whole generated more questions than answers (Hua et al, 2018; Kilpert et al, 2012; Luana S.F.…”
Section: Introductionmentioning
confidence: 99%
“…These include the horse, but also the donkey (Kimura et al 2011), and a range of extinct equine species such as the hydruntine European ass, which flourished in Central and Western Europe at least until the Iron Age (Orlando et al 2006); the giant Cape zebra (Orlando et al 2009); as well as North and South American specimens (Vilà et al 2001;Weinstock et al 2005;Vilstrup et al 2013;Sarkissian et al 2015). The horse itself currently holds the world record for the oldest genome ever sequenced, which was characterized from bone material preserved in the Yukon permafrost and dated to 560-780 KYA .…”
Section: Predomestication Timesmentioning
confidence: 99%
“…In the near future, we expect that this approach will be superseded by target-enrichment methods coupled with high-throughput sequencing. In horses, such approaches have been applied to only a limited number of loci (Vilstrup et al 2013;Sarkissian et al 2015), but recent procedures enable genotyping millions of loci genome wide (Fu et al 2016), and even entire chromosomes (Fu et al 2013) and genomes (Carpenter et al 2013). This will likely facilitate the identification of the whole series of genetic modifications that have accompanied the recent evolutionary history of this family, domestication and extinction processes included.…”
Section: Predomestication Timesmentioning
confidence: 99%